2020
DOI: 10.1016/j.seppur.2019.116139
|View full text |Cite
|
Sign up to set email alerts
|

Waste-based biosorbents as cost-effective alternatives to commercial adsorbents for the retention of fluoxetine from water

Abstract: The goal of this study is to demonstrate that waste-based biosorbents can be cost-effective and green alternatives to commercial adsorbents for the retention of pharmaceuticals. Adsorption kinetics and equilibrium measurements allowed the determination of the adsorption capacity of commercial adsorbents (GAC-granular activated carbon and two synthetic zeolites) and waste-based biosorbents (SCG-spent coffee grounds, pine bark and cork waste) for the retention of fluoxetine from water. For commercial adsorbents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 29 publications
1
28
0
2
Order By: Relevance
“…In comparison with HTC, the environmental, energetic and economical costs of pyrolysis are much higher, which confers an additional value to the present adsorbents. In addition, it has to be highlighted that the ACs produced in this work show a better performance towards fluoxetine than biosorbents prepared from biomass wastes as those reported in [19], which attained Q o values in the range of 6.4-14.3 mg g −1 . The values of the affinity constant, K L , are greater for carbon dioxide ACs.…”
Section: Fluoxetine Adsorptionmentioning
confidence: 81%
See 1 more Smart Citation
“…In comparison with HTC, the environmental, energetic and economical costs of pyrolysis are much higher, which confers an additional value to the present adsorbents. In addition, it has to be highlighted that the ACs produced in this work show a better performance towards fluoxetine than biosorbents prepared from biomass wastes as those reported in [19], which attained Q o values in the range of 6.4-14.3 mg g −1 . The values of the affinity constant, K L , are greater for carbon dioxide ACs.…”
Section: Fluoxetine Adsorptionmentioning
confidence: 81%
“…Despite its abundancy of aquatic streams, only few pieces of research have studied the removal of fluoxetine by adsorption, and most of them have used commercial ACs, alone or combined with carbon nanotubes [18]. In the frame of biomass or waste based adsorbents, the recent work of Silva et al [19] can be highlighted, where the biosorption of fluoxetine on several biomass sources (spent coffee grounds, pine bark and cork waste) was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was first described as an adsorbent in 2005, [20] its use in environmental applications for the removal of a variety of organic and inorganic pollutants has gained considerable attention, and a large number of research articles, as well as reviews, covering this approach have been published [17,[21][22][23][24][25][26]. The cork employment in sample preparation for microextraction purposes was firstly reported in…”
Section: Corkmentioning
confidence: 99%
“…Therefore, its formidable characteristics are promising resources with potential application on adsorption technologies [18]. Herewith cork is a natural, cheap, renewable, fully sustainable, and biodegradable raw material with a very relevant advantage over other carbonaceous materials to be explored as a sorbent in many applications [19].Since it was first described as an adsorbent in 2005, [20] its use in environmental applications for the removal of a variety of organic and inorganic pollutants has gained considerable attention, and a large number of research articles, as well as reviews, covering this approach have been published [17,[21][22][23][24][25][26]. The cork employment in sample preparation for microextraction purposes was firstly reported in…”
mentioning
confidence: 99%
“…Composted residues from cork were used as plant growth media to suppress plant diseases [3], and hydrological properties of substrates based on industrial cork residue have also been reported [4]. Recently, their adsorption properties, such as fining agent in wines, were stated [5], and some works showed that cork wastes are cost-effective and green alternatives to the retention of contaminants from water [6][7][8][9]. However, to the best of our knowledge, few works were reported regarding their revalorization for the food industry.…”
Section: Introductionmentioning
confidence: 99%